Modified fly ash reinforced mining phenolic aldehyde filling material and preparation method thereof
By combining modified fly ash with phenolic resin, the problems of brittleness and fly ash pollution of phenolic foam materials are solved, and modified fly ash reinforced minerals with high compression resistance and flame retardancy are prepared. Phenolic filling materials have achieved resource utilization of fly ash and improved coal mine safety.
Patent Information
- Application Number
- CN202411424134.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-03
AI Technical Summary
The existing phenolic foam materials are highly brittle and have severe slag loss in coal mine filling, and the environmental pollution problem of fly ash has not been effectively solved, making it difficult to achieve resource utilization.
Modified fly ash and phenolic resin are used to combine with silane coupling agent. The mechanical properties and interface bond strength of the material are enhanced by the low-temperature foaming technology. Fly ash reinforced phenolic filling material for minerals.
It improves the compression resistance and flame retardancy of the material, reduces slag dropping and combustion temperature, realizes the resource utilization of fly ash, enhances the sealing capacity of gas gas, and has a simple process and low cost.
Smart Images

Figure CN119241981A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of phenolic filling materials for mining, and in particular to a modified fly ash reinforced phenolic filling material for mining and a preparation method thereof. Background Art
[0002] There are two main reasons for coal mine accidents: explosions and suffocation caused by gas leakage in coal mines; and collapse of coal mines caused by reduced bearing capacity of the strata. Therefore, developing a lightweight material that can be used for filling and plugging leaks is an effective solution to the frequent occurrence of coal mine accidents.
[0003] Phenolic foam materials have attracted extensive attention in the fields of building insulation and coal mine filling due to their excellent properties such as low thermal conductivity, no dripping during combustion, and low toxic gas emissions. For example, in coal mining, coal mine collapse, mine water gushing, and gas leakage often occur, which can easily cause serious casualties and ecological pollution. At this time, the good adhesion and filling properties of phenolic foam are used to fill and plug these areas, which can effectively prevent the coal seam from further moving and cracking, and improve the safety and stability of the coal mine. However, the characteristics of phenolic foam such as high brittleness, severe slag, and high reaction temperature make it more difficult in the actual construction process. Therefore, it is urgent to develop a phenolic foam composite material that can be foamed at low temperature with high toughness and less slag.
[0004] Fly ash is a powdery solid waste discharged after coal-fired power plants burn coal powder. It is mainly composed of silicon dioxide (SiO2), aluminum oxide (Al2O3), iron oxide (Fe2O3), calcium oxide (CaO) and a small amount of other oxides. Its diameter usually ranges from 1 to 150 microns. Its reserves are huge and the price is low. However, a large amount of waste fly ash will cause serious pollution to terrestrial and marine ecosystems. Therefore, how to effectively utilize this waste resource has become very important. Summary of the invention
[0005] The purpose of the present invention is to provide a modified fly ash reinforced phenolic filling material for mining and a preparation method thereof. The use of modified fly ash to reinforce the phenolic filling material can not only improve the mechanical properties and slagging properties of the phenolic filling material, but also reduce pollution to the environment and realize the resource utilization of solid waste.
[0006] To achieve the above-mentioned object, the present invention provides a modified fly ash reinforced phenolic filling material for mining, which comprises the following components in parts by weight: 180-220 parts of phenolic resin, 0.8-6 parts of surfactant, 5-20 parts of foaming agent, 5-40 parts of modified fly ash, and 10-40 parts of curing agent.
[0007] Preferably, the modified fly ash is fly ash modified by using a silane coupling agent.
[0008] More preferably, the silane coupling agent is KH560.
[0009] The present invention utilizes the silanol group in the silane coupling agent KH560 to undergo a condensation reaction with the hydroxyl group on the surface of the fly ash in an ethanol aqueous solution, and the epoxy group of the silane coupling agent KH560 reacts with the phenolic hydroxyl group and the hydroxymethyl group in the phenolic resin under the catalytic action of the acidic curing agent, so that the silane coupling agent KH560 connects the fly ash and the phenolic resin in the form of a molecular bridge, thereby enhancing the interface bonding strength between the fly ash and the phenolic foam and enhancing the compressive strength of the phenolic filling material for mining.
[0010] Preferably, the surfactant is one or more of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate and DC-193.
[0011] Preferably, the foaming agent is one or more of n-pentane, water and sodium bicarbonate.
[0012] Preferably, the curing agent is a complex of p-toluenesulfonic acid, phosphoric acid and benzenesulfonic acid, and the mass ratio of toluenesulfonic acid, phosphoric acid and benzenesulfonic acid is 2:1:1.
[0013] The method for preparing the modified fly ash reinforced phenolic filling material for mining comprises the following steps: S1. Pour fly ash into an ethanol aqueous solution containing a silane coupling agent, stir at room temperature for 1 hour, and then perform centrifugal cleaning, drying, and ball milling to obtain surface-modified fly ash; and activate the surface-modified fly ash to obtain modified fly ash; S2, add phenol to the reaction container for preheating, then add NaOH and paraformaldehyde, continue to react for 2-3 hours after heating, regularly detect water solubility during this period, add urea after the water solubility reaches the target value, and finally adjust the pH to neutral to obtain phenolic resin; S3, take the phenolic resin prepared in S2, add a surfactant, a foaming agent and modified fly ash, and stir thoroughly until uniform, then add a curing agent, stir quickly and pour into a mold for low-temperature foaming, and finally obtain a modified fly ash reinforced mining phenolic filling material.
[0014] Preferably, in S1, the volume ratio of ethanol to water in the ethanol aqueous solution is 9:1.
[0015] Preferably, in S1, the activation is performed by keeping the mixture at 80-100° C. for 1-3 hours and then cooling the mixture to room temperature.
[0016] Preferably, in S2, the amounts of the components used are 100-600 parts by weight of phenol, 1-6 parts by weight of NaOH, 45-350 parts by weight of paraformaldehyde, and 5-20 parts by weight of urea.
[0017] Preferably, in S2, the target value of water solubility is 300-400%.
[0018] Mechanism of the present invention: The present invention evenly disperses KH560 modified fly ash in the phenolic foam matrix, so that the external stress is effectively distributed in the foam pores, the resistance to external forces is enhanced, and the introduction of flexible siloxane long chains in the rigid molecular structure of the foam can reduce the crack expansion speed, absorb a certain amount of destructive energy, and make the phenolic foam composite material (i.e., the modified fly ash reinforced mining phenolic filling material) show higher anti-compression deformation ability under the action of external load. In addition, due to the increase in viscosity of the phenolic foam composite material system and the catalytic curing effect of fly ash, the foam structure is transformed from a multi-open-cell structure to a continuous closed-cell structure, the release of combustible volatiles and the transfer of heat during the foam combustion process are suppressed, the phenolic foam composite material shows excellent heat insulation and flame retardant properties, and the maximum reaction temperature inside is reduced. In addition, SiO2 and siloxane in the fly ash consume oxygen to form a silicon dioxide hybrid carbon layer with a higher degree of graphitization, and this stable and dense carbon layer not only blocks heat and feeds oxygen back to the foam matrix, but also suppresses the release of combustible volatiles and toxic gases.
[0019] Beneficial effects of the present invention: (1) The modified fly ash reinforced phenolic filling material for mining provided by the present invention mixes the powdered solid waste discharged after burning coal powder in coal-fired power plants with phenolic foam, thereby realizing the resource utilization of fly ash and providing a new idea for the sustainable recycling of fly ash. It has important practical conversion value for the recycling of fly ash, not only providing a new strategy for the recycling of solid waste, but also providing inspiration for the sustainable development of low reaction heat and multifunctional integrated mining filling materials.
[0020] (2) The present invention provides a method for preparing a modified fly ash reinforced phenolic filling material for mining, which can be achieved at low temperature, has no special requirements for experimental equipment, avoids the use of expensive instruments, and the stirring and heating operations are safe and simple. The fly ash modification can be completed at room temperature, avoiding energy waste. It is safe and low-cost and can be applied on a large scale.
[0021] (3) The present invention provides a modified fly ash reinforced phenolic filling material for mining. The surface energy of fly ash is reduced and its activity is stimulated by surface modification with organic siloxane, so that it can be completely embedded in the phenolic foam matrix, achieving a close bond between the organic-inorganic two phases, and strengthening the resistance of the phenolic foam matrix to external stress; the continuous closed-cell structure of different sizes blocks the release of combustible volatile gases and the transfer of heat; and the formed silicon dioxide hybrid carbon layer with a higher degree of graphitization enhances the flame retardancy of the phenolic foam composite material. In the present invention, the tunnel simulation test verifies that the composite material has a strong gas blocking ability, proving its effectiveness in preventing gas penetration.
[0022] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The microscopic morphology and physical image of the mining phenolic filling material prepared in Example 2, Comparative Example 2 and Comparative Example 4 of the present invention are shown in FIG. in Figure 1 a in the figure is the microscopic morphology of comparative example 4, Figure 1 b is the microscopic morphology of comparative example 2, Figure 1 c in the figure is the microscopic morphology of Example 2, Figure 1 d in is the physical picture of comparative example 4, Figure 1 e in the figure is a physical picture of comparative example 2, Figure 1 f is a physical picture of Example 2; Figure 2 is a microscopic morphology of the mining phenolic filling material obtained in Example 2, Comparative Example 2 and Comparative Example 4 of the present invention after combustion, in Figure 2 a in the figure is the microscopic morphology of comparative example 4 after combustion. Figure 2 b is the microscopic morphology of comparative example 2 after combustion, Figure 2 c is the microscopic morphology of Example 2 after combustion; Figure 3 It is a schematic diagram of gas blocking of the modified fly ash reinforced mining phenolic filling material under different pressures in Example 2 of the present invention. DETAILED DESCRIPTION
[0024] The present invention is further described below in conjunction with the accompanying drawings and embodiments. Unless otherwise defined, the technical terms or scientific terms used in the present invention should be the common meanings understood by people with ordinary skills in the field to which the present invention belongs. The above-mentioned features or features mentioned in the specific examples mentioned in the present invention can be combined arbitrarily, and these specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0025] Example 1 The present invention provides a modified fly ash reinforced phenolic filling material for mining, and the preparation method thereof comprises the following steps: S1. Pour fly ash into an ethanol aqueous solution containing a silane coupling agent, wherein the volume ratio of ethanol to water in the ethanol aqueous solution is 9:1, stir at room temperature for 1 hour, perform centrifugal washing, drying, and ball milling to obtain surface-modified fly ash; keep the surface-modified fly ash at 100°C for 1 hour and then cool it to room temperature to obtain activated modified fly ash; S2, add 600g of phenol to a three-necked flask with a stirrer, a condenser and a thermometer, heat to 70°C for preheating, then start to drip 2g of NaOH solution (add once every 10min thereafter, a total of 6g), stir for 10min in advance to enhance the reactivity of phenol; then add 115g of paraformaldehyde every 15min, add three times in total, heat to 80°C after 1h, and continue to react for 2-3h. During this process, the water solubility of the resin needs to be regularly tested. When the water solubility is expected to reach 300-400%, turn off the heating and add 20g of urea to react for 10min, and finally drip a small amount of formic acid to adjust the pH to neutral to obtain a phenolic resin; S3, take 200g of phenolic resin prepared in S2, add 1.6g of sodium dodecylbenzene sulfonate and 3.6g of DC-193 as surfactants, 20g of n-pentane as foaming agent, 10g of modified fly ash, stir quickly and evenly, add 40g of curing agent (the composite acid used in the curing agent is p-toluenesulfonic acid: phosphoric acid: benzenesulfonic acid with a mass ratio of 2:1:1), stir mechanically for 20s, and immediately pour into a mold for low-temperature foaming to finally obtain modified fly ash reinforced mining phenolic filling material.
[0026] Example 2 The present invention provides a modified fly ash reinforced phenolic filling material for mining, and the preparation method thereof comprises the following steps: S1. Pour fly ash into an ethanol aqueous solution containing a silane coupling agent, wherein the volume ratio of ethanol to water in the ethanol aqueous solution is 9:1, stir at room temperature for 1 hour, perform centrifugal washing, drying, and ball milling to obtain surface-modified fly ash; keep the surface-modified fly ash at 100°C for 1 hour and then cool it to room temperature to obtain activated modified fly ash; S2, add 600g of phenol to a three-necked flask with a stirrer, a condenser and a thermometer, heat to 70°C for preheating, then start to drip 2g of NaOH solution (add once every 10min thereafter, a total of 6g), stir for 10min in advance to enhance the reactivity of phenol; then add 115g of paraformaldehyde every 15min, add three times in total, heat to 80°C after 1h, and continue to react for 2-3h. During this process, the water solubility of the resin needs to be regularly tested. When the water solubility is expected to reach 300-400%, turn off the heating and add 20g of urea to react for 10min, and finally drip a small amount of formic acid to adjust the pH to neutral to obtain a phenolic resin; S3, take 200g of phenolic resin prepared in S2, add 1.6g of sodium dodecylbenzene sulfonate and 3.6g of DC-193 as surfactants, 20g of n-pentane as foaming agent, 20g of modified fly ash, and quickly stir evenly before adding 40g of curing agent (the composite acid used in the curing agent is p-toluenesulfonic acid: phosphoric acid: benzenesulfonic acid with a mass ratio of 2:1:1), stir mechanically for 20s, and immediately pour into a mold for low-temperature foaming to finally obtain modified fly ash reinforced mining phenolic filling material.
[0027] Example 3 The present invention provides a modified fly ash reinforced phenolic filling material for mining, and the preparation method thereof comprises the following steps: S1. Pour fly ash into an ethanol aqueous solution containing a silane coupling agent, wherein the volume ratio of ethanol to water in the ethanol aqueous solution is 9:1, stir at room temperature for 1 hour, perform centrifugal washing, drying, and ball milling to obtain surface-modified fly ash; keep the surface-modified fly ash at 100°C for 1 hour and then cool it to room temperature to obtain activated modified fly ash; S2, add 600g of phenol to a three-necked flask with a stirrer, a condenser and a thermometer, heat to 70°C for preheating, then start to drip 2g of NaOH solution (add once every 10min thereafter, a total of 6g), stir for 10min in advance to enhance the reactivity of phenol; then add 115g of paraformaldehyde every 15min, add three times in total, heat to 80°C after 1h, and continue to react for 2-3h. During this process, the water solubility of the resin needs to be regularly tested. When the water solubility is expected to reach 300-400%, turn off the heating and add 20g of urea to react for 10min, and finally drip a small amount of formic acid to adjust the pH to neutral to obtain a phenolic resin; S3, take 200g of phenolic resin prepared in S2, add 1.6g of sodium dodecylbenzene sulfonate and 3.6g of DC-193 as surfactants, 20g of n-pentane as foaming agent, 40g of modified fly ash, stir quickly and evenly, add 40g of curing agent (the composite acid used in the curing agent is p-toluenesulfonic acid: phosphoric acid: benzenesulfonic acid with a mass ratio of 2:1:1), stir mechanically for 20s, and immediately pour into a mold for low-temperature foaming to finally obtain modified fly ash reinforced mining phenolic filling material.
[0028] Example 4 The present invention provides a modified fly ash reinforced phenolic filling material for mining, and the preparation method thereof comprises the following steps: S1. Pour fly ash into an ethanol aqueous solution containing a silane coupling agent, wherein the volume ratio of ethanol to water in the ethanol aqueous solution is 9:1, stir at room temperature for 1 hour, perform centrifugal washing, drying, and ball milling to obtain surface-modified fly ash; keep the surface-modified fly ash at 100°C for 1 hour and then cool it to room temperature to obtain activated modified fly ash; S2, add 600g of phenol to a three-necked flask with a stirrer, a condenser and a thermometer, heat to 70°C for preheating, then start to drip 2g of NaOH solution (add once every 10min thereafter, a total of 6g), stir for 10min in advance to enhance the reactivity of phenol; then add 115g of paraformaldehyde every 15min, add three times in total, heat to 80°C after 1h, and continue to react for 2-3h. During this process, the water solubility of the resin needs to be regularly tested. When the water solubility is expected to reach 300-400%, turn off the heating and add 20g of urea to react for 10min, and finally drip a small amount of formic acid to adjust the pH to neutral to obtain a phenolic resin; S3, take 200g of phenolic resin prepared in S2, add 1.6g of sodium dodecylbenzene sulfonate and 3.6g of DC-193 as surfactants, 20g of n-pentane as foaming agent, 20g of modified fly ash, and add 40g of curing agent (the composite acid used in the curing agent is p-toluenesulfonic acid: phosphoric acid with a mass ratio of 2:1) after rapid stirring, and immediately pour into a mold for low-temperature foaming after mechanical stirring for 20s, and finally obtain modified fly ash reinforced mining phenolic filling material.
[0029] Example 5 The present invention provides a modified fly ash reinforced phenolic filling material for mining, and the preparation method thereof comprises the following steps: S1. Pour fly ash into an ethanol aqueous solution containing a silane coupling agent, wherein the volume ratio of ethanol to water in the ethanol aqueous solution is 9:1, stir at room temperature for 1 hour, perform centrifugal washing, drying, and ball milling to obtain surface-modified fly ash; keep the surface-modified fly ash at 100°C for 1 hour and then cool it to room temperature to obtain activated modified fly ash; S2, add 600g of phenol to a three-necked flask with a stirrer, a condenser and a thermometer, heat to 70°C for preheating, then start to drip 2g of NaOH solution (add once every 10min thereafter, a total of 6g), stir for 10min in advance to enhance the reactivity of phenol; then add 115g of paraformaldehyde every 15min, add three times in total, heat to 80°C after 1h, and continue to react for 2-3h. During this process, the water solubility of the resin needs to be regularly tested. When the water solubility is expected to reach 300-400%, turn off the heating and add 20g of urea to react for 10min, and finally drip a small amount of formic acid to adjust the pH to neutral to obtain a phenolic resin; S3, take 200g of phenolic resin prepared in S2, add 1.6g of sodium dodecylbenzene sulfonate and 3.6g of DC-193 as surfactants, 20g of n-pentane as foaming agent, 10g of modified fly ash, stir quickly and evenly, add 40g of curing agent (the composite acid used in the curing agent is p-toluenesulfonic acid: phosphoric acid with a mass ratio of 2:1), stir mechanically for 20s, and immediately pour into a mold for low-temperature foaming to finally obtain modified fly ash reinforced mining phenolic filling material.
[0030] Comparative Example 1 A fly ash reinforced phenolic filling material for mining, the preparation method of which comprises the following steps: S1, pouring the fly ash into a ball mill after drying, and mixing it thoroughly to obtain unmodified fly ash; S2, add 600g of phenol to a three-necked flask with a stirrer, a condenser and a thermometer, heat to 70°C for preheating, then start to drip 2g of NaOH solution (add once every 10min thereafter, a total of 6g), stir for 10min in advance to enhance the reactivity of phenol; then add 115g of paraformaldehyde every 15min, add three times in total, heat to 80°C after 1h, and continue to react for 2-3h. During this process, the water solubility of the resin needs to be regularly tested. When the water solubility is expected to reach 300-400%, turn off the heating and add 20g of urea to react for 10min, and finally drip a small amount of formic acid to adjust the pH to neutral to obtain a phenolic resin; S3, take 200g of phenolic resin prepared in S2, add 1.6g of sodium dodecylbenzene sulfonate and 3.6g of DC-193 as surfactants, 20g of n-pentane as foaming agent, 10g of unmodified fly ash, stir quickly and evenly, add 40g of curing agent (the composite acid used in the curing agent is p-toluenesulfonic acid: phosphoric acid: benzenesulfonic acid with a mass ratio of 2:1:1), stir mechanically for 20s, and immediately pour into a mold for low-temperature foaming to finally obtain modified fly ash reinforced mining phenolic filling material.
[0031] Comparative Example 2 A fly ash reinforced phenolic filling material for mining, the preparation method of which comprises the following steps: S1, pouring the fly ash into a ball mill after drying, and mixing it thoroughly to obtain unmodified fly ash; S2, add 600g of phenol to a three-necked flask with a stirrer, a condenser and a thermometer, heat to 70°C for preheating, then start to drip 2g of NaOH solution (add once every 10min thereafter, a total of 6g), stir for 10min in advance to enhance the reactivity of phenol; then add 115g of paraformaldehyde every 15min, add three times in total, heat to 80°C after 1h, and continue to react for 2-3h. During this process, the water solubility of the resin needs to be regularly tested. When the water solubility is expected to reach 300-400%, turn off the heating and add 20g of urea to react for 10min, and finally drip a small amount of formic acid to adjust the pH to neutral to obtain a phenolic resin; S3, take 200g of phenolic resin prepared in S2, add 1.6g of sodium dodecylbenzene sulfonate and 3.6g of DC-193 as surfactants, 20g of n-pentane as foaming agent, 20g of unmodified fly ash, and quickly stir evenly before adding 40g of curing agent (the composite acid used in the curing agent is p-toluenesulfonic acid: phosphoric acid: benzenesulfonic acid with a mass ratio of 2:1:1), stir mechanically for 20s, and immediately pour into a mold for low-temperature foaming to finally obtain modified fly ash reinforced mining phenolic filling material.
[0032] Comparative Example 3 A fly ash reinforced phenolic filling material for mining, the preparation method of which comprises the following steps: S1, pouring the fly ash into a ball mill after drying, and mixing it thoroughly to obtain unmodified fly ash; S2, add 600g of phenol to a three-necked flask with a stirrer, a condenser and a thermometer, heat to 70°C for preheating, then start to drip 2g of NaOH solution (add once every 10min thereafter, a total of 6g), stir for 10min in advance to enhance the reactivity of phenol; then add 115g of paraformaldehyde every 15min, add three times in total, heat to 80°C after 1h, and continue to react for 2-3h. During this process, the water solubility of the resin needs to be regularly tested. When the water solubility is expected to reach 300-400%, turn off the heating and add 20g of urea to react for 10min, and finally drip a small amount of formic acid to adjust the pH to neutral to obtain a phenolic resin; S3, take 200g of phenolic resin prepared in S2, add 1.6g of sodium dodecylbenzene sulfonate and 3.6g of DC-193 as surfactants, 20g of n-pentane as foaming agent, 40g of unmodified fly ash, stir quickly and evenly, add 40g of curing agent (the composite acid used in the curing agent is p-toluenesulfonic acid: phosphoric acid: benzenesulfonic acid with a mass ratio of 2:1:1), stir mechanically for 20s, and immediately pour into a mold for low-temperature foaming to finally obtain modified fly ash reinforced mining phenolic filling material.
[0033] Comparative Example 4 A phenolic filling material for mining, the preparation method of which comprises the following steps: S1. Add 600g of phenol to a three-necked flask with a stirrer, a condenser and a thermometer, heat to 70°C for preheating, then start to drip 2g of NaOH solution (add once every 10 minutes thereafter, a total of 6g), and stir for 10 minutes in advance to enhance the reactivity of phenol; then add 115g of paraformaldehyde every 15 minutes for a total of three times, heat to 80°C after 1 hour, and continue to react for 2-3 hours. During this process, the water solubility of the resin needs to be regularly tested. When the water solubility is expected to reach 300-400%, turn off the heating and add 20g of urea to react for 10 minutes, and finally drip a small amount of formic acid to adjust the pH to neutral to obtain a phenolic resin; S2, take 200g of phenolic resin prepared in S1, add 1.6g of sodium dodecylbenzene sulfonate and 3.6g of DC-193, and 20g of n-pentane, a surfactant, and quickly stir until uniform, then add 40g of curing agent (the composite acid used in the curing agent is p-toluenesulfonic acid: phosphoric acid: benzenesulfonic acid in a mass ratio of 2:1:1), stir mechanically for 20s, and immediately pour into a mold for low-temperature foaming to finally obtain a modified fly ash reinforced mining phenolic filling material.
[0034] The performance tests were conducted on the modified fly ash reinforced phenolic filling materials for mining prepared in Examples 1-5 and the phenolic filling materials for mining prepared in Comparative Examples 1-4. The results are shown in Table 1.
[0035] Table 1 Performance test data of Examples 1-5 and Comparative Examples 1-4
[0036] As can be seen from Table 1, the phenolic filling material for mining prepared by using silane coupling agent modified fly ash in the present invention is superior to the phenolic filling material for mining prepared by using unmodified fly ash in terms of apparent density, compressive strength, oxygen index, pulverization rate and thermal conductivity. However, when the addition amount of modified fly ash or unmodified fly ash exceeds 20 parts, the various properties of both materials decline significantly, which may be caused by the large amount of agglomeration of fly ash.
[0037] Compared with pure phenolic foam, the compressive strength and oxygen index of the mining phenolic filling material prepared by silane coupling agent modified fly ash are improved, and the pulverization rate is reduced. Especially when the addition amount of silane coupling agent modified fly ash is 10 parts, the structure of the composite material changes from a multi-open-pore structure to a continuous closed-pore structure, which inhibits the release of combustible volatiles and the transfer of heat during the combustion of the foam, making the composite material exhibit excellent thermal insulation and flame retardancy, and reducing its internal maximum reaction temperature. Figure 1-2 The tunnel simulation test verified that the composite material has strong gas blocking ability and proved its effectiveness in preventing gas penetration. Figure 3 shown.
[0038] In summary, compared with pure phenolic foam, the modified fly ash reinforced mining phenolic filling material provided by the present invention exhibits advantages such as better compression resistance, heat insulation, flame retardancy and low slagging.
[0039] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A modified fly ash reinforced phenolic filling material for mining, characterized in that: The composition includes the following components in parts by weight: 180-220 parts of phenolic resin, 0.8-6 parts of surfactant, 5-20 parts of foaming agent, 5-40 parts of modified fly ash and 10-40 parts of curing agent.
2. The modified fly ash reinforced phenolic filling material for mining according to claim 1, characterized in that: Modified fly ash is fly ash modified by using silane coupling agent.
3. The modified fly ash reinforced phenolic filling material for mining according to claim 1, characterized in that: The surfactant is one or more of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate and DC-193.
4. The modified fly ash reinforced phenolic filling material for mining according to claim 1, characterized in that: The foaming agent is one or more of n-pentane, water and sodium bicarbonate.
5. The modified fly ash reinforced phenolic filling material for mining according to claim 1, characterized in that: The curing agent is a complex of p-toluenesulfonic acid, phosphoric acid and benzenesulfonic acid, and the mass ratio of toluenesulfonic acid, phosphoric acid and benzenesulfonic acid is 2:1:
1.
6. A method for preparing the modified fly ash reinforced mining phenolic filling material according to any one of claims 1 to 5, characterized in that: The following steps are included: S1. Pour fly ash into an ethanol aqueous solution containing a silane coupling agent, stir at room temperature for 1 hour, and then perform centrifugal cleaning, drying, and ball milling to obtain surface-modified fly ash; and activate the surface-modified fly ash to obtain modified fly ash; S2, add phenol to the reaction container for preheating, then add NaOH and paraformaldehyde, continue to react for 2-3 hours after heating, regularly detect water solubility during this period, add urea after the water solubility reaches the target value, and finally adjust the pH to neutral to obtain phenolic resin; S3, take the phenolic resin prepared in S2, add a surfactant, a foaming agent and modified fly ash, and stir thoroughly until uniform, then add a curing agent, stir quickly and pour into a mold for low-temperature foaming, and finally obtain a modified fly ash reinforced mining phenolic filling material.
7. The method for preparing the modified fly ash reinforced phenolic filling material for mining according to claim 6, characterized in that: In S1, the volume ratio of ethanol to water in the ethanol-water solution is 9:
1.
8. The method for preparing the modified fly ash reinforced phenolic filling material for mining according to claim 6, characterized in that: In S1, activation is performed by keeping the mixture at 80-100°C for 1-3 hours and then cooling the mixture to room temperature.
9. The method for preparing the modified fly ash reinforced phenolic filling material for mining according to claim 6, characterized in that: In S2, the amounts of the components used are, by weight, 100-600 parts of phenol, 1-6 parts of NaOH, 45-350 parts of paraformaldehyde, and 5-20 parts of urea.
10. The method for preparing the modified fly ash reinforced phenolic filling material for mining according to claim 6, characterized in that: In S2, the target value of water solubility is 300~400%.
